EFEK PEMBERIAN ZEOLIT PADA TRANSPORTASI IKAN LELE (Clarias sp.) - Fauzan B, M. Iqbal; Syamsunarno, Mas Bayu; Putra, Achmad Noerkhaerin (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2021)
Catfish is a freshwater fish that is widely cultivated in almost all parts of Indonesia. Potential business catfish, and many enthusiasts, the difference in the distance between the location of the cultivator and the location of the seller causes the need for fish transportation to support production activities. Fish transportation can be defined as an act of moving fish alive from one place to another in which measures are taken to keep the fish survival high up to its destination. One of the efforts to streamline transportation costs is to increase the density of fish in the transportation medium. The high density of fish in closed transportation media is a problem because the demand for oxygen (O2) is also increasing. This transportation research was carried out on March 7 - 8 2020 along the roads of Pandeglang city, Pandeglang district, Serang city, Serang district and Cilegon city. The results of the study in each treatment showed a survival rate value (100%). The test results show that in each treatment the average ranges from 27.7-27.9oC, this shows that each treatment has no effect on temperature changes. The pH parameter in each treatment shows a relatively stable number with an average value in treatment A, B and C of 6.1 mg / L.